(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article analyzes the concept of the conditional deposit (escrow) agreement. The main legal characteristics of the contract and the specific features of its legal regulation are considered. The escrow contract is considered consensual (based on an agreement between the parties), but depending on the deposited object, it may also be real (executed by transferring the property). The article emphasizes the two-sided obligation nature of the contract, which involves parties such as the depositor, beneficiary, and escrow agent. The conditional deposit agreement ensures the protection of the rights and legal interests of the parties concerning the transfer of property obligations.